PERUBAHAN PERILAKU MASYARAKAT DALAM MEMBAYAR ZAKAT DI KAMPUNG ZAKAT (Studi Pada Desa Banjarwaru, Kecamatan Nusawungu, Kabupaten Cilacap) - Sri Malika Sari; Rahhmini Hadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
Zakat is one of the pillars of Islam that holds significant socio-economic functions, serving not only as an individual act of worship but also as an instrument of wealth redistribution to reduce social inequality. Its practice has undergone various dynamics in line with social, economic, and institutional transformations. In the context of Banjarwaru Village, which has been designated as a Kampung Zakat (Zakat Village), this phenomenon reflects a notable transformation in community behavior regarding zakat payment. This study aims to: (1) analyze the behavioral patterns of the community and the factors influencing their zakat payment practices before and after the establishment of the Kampung Zakat; (2) examine the roles of religious leaders and local government in encouraging behavioral change; and (3) analyze the transformation of zakat-paying behavior in Banjarwaru through the perspectives of the Theory of Planned Behavior (TPB), Diffusion of Innovations, and Role Theory.This research employs a qualitative descriptive approach with a case study method. Primary data were obtained through in-depth interviews with religious leaders, local government officials, and community members, while secondary data were collected from literature, regulations, and institutional documents of the Zakat Collection Unit (UPZ). Data were analyzed using Miles and Huberman’s interactive model, consisting of reduction, presentation, and conclusion drawing.The study concludes three main findings. First, the zakat-paying behavior of Banjarwaru’s community has shifted from a traditional, personal pattern toward an institutionalized system through the UPZ, driven by growing religious awareness, institutional trust, and the tangible benefits of productive zakat for village welfare. Second, religious leaders play a moral role in strengthening religious legitimacy, while local government acts as a structural facilitator through regulations, support, and the integration of zakat into village development programs. Third, analysis using TPB, Diffusion of Innovations, and Role Theory demonstrates that this transformation results from the integration of individual attitude changes, diffusion of innovation through social networks, and consistent role enactment, leading zakat payment in Banjarwaru to develop into a sustainable collective practice.